Development of autonomic heart rate modulations during childhood and adolescence - Helánová, Kateřina; Šišáková, Martina; Hnatkova, Katerina; Novotný, Tomáš; Andršová, Irena; Malik, Marek (Pflugers Archiv : European journal of physiology, 2024)
Autonomic control of heart rate is well known in adult subjects, but limited data are available on the development of the heart rate control during childhood and adolescence. Continuous 12-lead electrocardiograms were recorded in 1045 healthy children and adolescents (550 females) aged 4 to 19 years during postural manoeuvres involving repeated 10-min supine, unsupported sitting, and unsupported standing positions. In each position, heart rate was measured, and heart rate variability indices were evaluated (SDNN, RMSSD, and high (HF) and low (LF) frequency components were obtained). Quasi-normalized HF frequency components were defined as qnHF = HF/(HF + LF). These measurements were, among others, related to age using linear regressions. In supine position, heart rate decreases per year of age were significant in both sexes but lower in females than in males. In standing position, these decreases per year of age were substantially lowered. RMSSD and qnHF indices were independent of age in supine position but significantly decreased with age in sitting and standing positions. Correspondingly, LF/HF proportions showed steep increases with age in sitting and standing positions but not in the supine position. The study suggests that baseline supine parasympathetic influence shows little developmental changes during childhood and adolescence but that in young children, sympathetic branch is less responsive to vagal influence. While vagal influences modulate cardiac periods in young and older children equally, they are less able to suppress the sympathetic influence in younger children.
Keywords: supinační poloha; Humans; dítě; Electrocardiography; Child; Female; mladý dospělý; dospělí; Heart Rate; lidé; předškolní dítě; Supine Position; Adult; ženské pohlaví; Male; srdeční frekvence; Adolescent; autonomní nervový systém; Young Adult; postura těla; Autonomic Nervous System; mužské pohlaví; Posture; Child, Preschool; mladiství; elektrokardiografie